Development of simple PWM inverter using photovoltaic cells - Soib, Taib; Yusmin, Sutanto; Abd Rahim, Abd Razak (Universiti Teknologi MARA (UiTM), 2009)
Organized by Universiti Teknologi MARA (UiTM), 16-17 July 2002 at Blue Wave Hotel, Shah Alam, Selangor.